Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1139/bcb-2019-0377
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of P-glycoprotein-mediated multidrug resistance by novel curcumin analogues in paclitaxel-resistant human breast cancer cells

Abstract: Multidrug resistance (MDR) is a major obstacle for successful cancer chemotherapy, and the main cause of MDR has been attributed to overexpression of P-glycoprotein (P-gp). In this present study, four P-gp modulators (E,E)-4,6-bis(styryl)-2-(substituted amino)-pyrimidines were evaluated for their activity in a breast cancer cell line overexpressing P-gp (LCC6MDR). The four modulators displayed significantly better P-gp modulating activity compared with the positive control verapamil (RF = 5.4), with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Substantial evidence exists for the role of P-gp in mediating taxane resistance in vitro; however, demonstrating its role in vivo has proven more difficult [61][62][63]. Nevertheless, ongoing research continues to explore the possibility of P-gp inhibition as a sufficient means for overcoming taxane resistance in vivo.…”
Section: Drug Transport and Effluxmentioning
confidence: 99%
“…Substantial evidence exists for the role of P-gp in mediating taxane resistance in vitro; however, demonstrating its role in vivo has proven more difficult [61][62][63]. Nevertheless, ongoing research continues to explore the possibility of P-gp inhibition as a sufficient means for overcoming taxane resistance in vivo.…”
Section: Drug Transport and Effluxmentioning
confidence: 99%
“…Even considering that natural anti-tumor drugs have lower potential compared to synthetic antitumor drugs, it has been shown that plant derived-natural compounds can be considered as adjuvants in cancer therapy along with other chemotherapeutic agents (Chen, Gao, Zhang, Chan, & Wong, 2019; Gokce Kutuk, Gokce, Kutuk, Gurses Cila, & Naziroglu, 2019). It is worth mentioning that naturally occurring compounds are able to sensitize cancer cells into chemotherapy-mediated apoptosis and cell cycle arrest (Gao et al, 2020;Zhao et al, 2019). So, plant derivednatural compounds are potential and beneficial compounds in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the migration of MDA-MB-231 cells was significantly reduced by the combination of KY-20-22 and paclitaxel compared to individual treatment ( Figure 8 A). Furthermore, various studies reported that curcumin and its analogs increase sensitivity to chemotherapeutic drugs by reversing the multidrug resistance of cancer cells [ 50 , 51 ]. The combined action of paclitaxel and KY-20-22 on TNBC cells may be due to the action of KY-20-22 on multidrug resistance proteins.…”
Section: Discussionmentioning
confidence: 99%